PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEDISIPLINAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI ( STUDI PADA PT. PLN (persero) Unit Pelaksana Kontruksi Jaringan Jawa Bali 7 (UPKJJB 7) SEMARANG ) - Yunita Anggi Anggraeni, 10.05.51.0028; Rahayuningsih, Sri (Students Journal of Economic and Management, 2014)
This study aims to examine and analyze the effect of transformational leadership, work discipline and motivation to work on the performance of employees of PT. PLN (Persero) UPKJJB 7 Semarang. The test data used in this study include the product moment test validity, reliability testing with Alpha Cronbrach, multiple linear regression analysis, t test to test and prove the research hypothesis. Data collected was tested for validity by the methods of analysis and tested reliabilitas with product moment coefficient alpha (Alpha Cronbrach), where the results of all data is valid and reliable. The results of the analysis and discussion demonstrate that: (1). Transformational leadership and significant positive effect on employee performance, the stronger the influence of the transformational leadership, then the performance employees in the company are also increasing; (2). Work discipline positive and significant effect on the performance of employees, the stronger the influence of the working discipline, then the performance employees in the company are also increasing; (3). Work motivation positive and significant effect on the performance of employees, the stronger the influence of work motivation, then the performance employees in the company are also increasing. Keywords: Transformational Leadership, Discipline of Work, Work Motivation, Employee Performance